Media Pembelajaran Film Pendek dalam Meningkatkan Keterampilan Menulis Teks Tanggapan - Najiyah, Nihayatun; Malikha, Usrin (Innovative: Journal Of Social Science Research, 2025)
This study aims to implement the use of short films as a learning medium in learning to write response texts for grade VII students of MTs Alhidayah Malang and analyze the level of response text writing skills of grade VII students of MTs Alhidayah Malang after using short films as a learning medium. This study uses a descriptive quantitative research method. The data source in this study is the results of response text writing scores in grade VII MTs Alhidayah with 6 male students and 5 female students, a total of 11 students. Based on the findings of students who understand the response text indicated by the overall student score is still very low with an average score of 51,81 before using short films and increased to 70,90 after using short films. Therefore, this study was specifically designed to analyze in depth the effect of using short films as a learning medium to improve students' response text writing skills at MTs Alhidayah.